The characterisation of Wickerhamomyces anomalus M15, a highly tolerant yeast for bioethanol production using seaweed derived medium - Turner, William; Greetham, Darren; Du, Chenyu (Frontiers in Bioengineering and Biotechnology, 2022)
Advanced generation biofuels have potential for replacing fossil fuels as society moves forward into a net-zero carbon future. Marine biomass is a promising source of fermentable sugars for fermentative bioethanol production; however the medium derived from seaweed hydrolysis often contains various inhibitors, such as salts that affected the bioethanol fermentation efficiency. In this study the stress tolerance of a marine yeast, Wickerhamomyces anomalus M15 was characterised. Specific growth rates analysis results showed that Wickerhamomyces anomalus M15 could tolerate up to 600 g/L glucose, 150 g/L xylose and 250 g/L ethanol, respectively. Using simulated concentrated seaweed hydrolysates, W. anomalus M15’s bioethanol production potential using macroalgae derived feedstocks was assessed, in which 5.8, 45.0 and 19.9 g/L ethanol was produced from brown, green and red seaweed based media. The fermentation of actual Ulva spp. hydrolysate harvested from UK shores resulted in a relatively low ethanol concentration (15.5 g/L) due to challenges that arose from concentrating the seaweed hydrolysate. However, fed-batch fermentation using simulated concentrated green seaweed hydrolysate achieved a concentration of 73 g/L ethanol in both seawater and RO water. Further fermentations conducted with an adaptive strain W. anomalus M15-500A showed improved bioethanol production of 92.7 g/L ethanol from 200 g/L glucose and reduced lag time from 93 hours to 24 hours in fermentation with an initial glucose concentration of 500 g/L. The results indicated that strains W. anomalus M15 and W. anomalus M15-500A have great potential for industrial bioethanol production using marine biomass derived feedstocks.